Life cycle cost analysis case study on corrosion remedial measures for concrete structures - Ho, Jin How (Penerbit UTM Press, 2004)
This paper discusses a short study on life cycle cost analysis (LCCA) on corrosion remedial measures for concrete bridges and marine structures, which are subjected to carbonation or ingress of sodium chloride from sea water and other sources. Life cycle costing software, Bridge LCC 2.0, was used to perform life cycle cost analyses on three case studies, based on net present value method. The analysis of the results showed that LCCA is capable of assisting engineers or transportation agencies to evaluate optimum maintenance decisions in corrosion-related problems. It can be used as an engineering economic analysis tool that helps in quantifying the differential costs and choosing the most cost-effective corrosion remedial measures. Life cycle costs for the remedial measures are influenced by many costing variables such as initial costs, periodic maintenance costs, frequency years and analysis period. The best practice of LCCA should not only consider agency expenditures but also user costs and sensitivity analysis throughout the service life of a remedial measure.